When Customer Insights Meet Business Constraints: Building a Go‐to‐Market Strategy for a Smart Home Offering in a Regulated Space. Issue 1 (24th January 2019) - KELLEY, ELIZABETH A.; DWELLEY, AMANDA E.
Abstract : This case draws on work in the energy efficiency industry where many utilities rely on data‐driven insights and decision‐making to encourage consumers to adopt energy‐saving products and behaviors. In this highly regulated industry, utility staff must show value through big data, and studies often rely exclusively on quantitative data analytics to create behavioral models to explain or predict behavior. However, purely data‐driven research often fails to answer questions about why customers behave a certain way, and what product or program managers and marketers can do about it. In this case study, the team from ILLUME Advising LLC (ILLUME), a research consultancy in the clean energy industry, illustrates how their cross‐functional team paired qualitative and quantitative research on residential home energy use. The case study draws on an exploratory market and segmentation study for an electric utility interested in engaging customers through a smart home product offering. The team used a mixed‐methods, hybrid research approach, cycling between quantitaive and qualitative methods, and refining the project concept and hypotheses before each stage of research. This approach set the stage for market and consumer insights that showed opportunities beyond the clients' original concept.